Evaluation of Infection Prevention and Control Programs at the Hospital Level Based on the World Health Organization Tool - Kiana Shirani; Arash Seifi; Elham Zarrazvand; Shirin Afhami; Rahim Raoufi Jahromi (International Journal of Preventive Medicine)
Background: Infection prevention and control (IPC) is a major component of health systems and affects both the health and safety of people who use health services and those who provide them. The Infection Prevention and Control Assessment Framework (IPCAF) is a tool for the assessment of IPC in healthcare centers. Methods: In the present study, we examined the hospitals of Tehran from this point of view. Results: Thirty-one hospitals were examined through IPCAF form. All the data were analyzed in SPSS version 25. Twenty-three centers (74.1%) were at the advanced level; 7 centers (22.5%) were at the intermediate level and only one center (3.2%) was at the minimum level. The lowest score was related to the field of education. There was no significant difference between private and public hospitals in terms of IPC score (P > 0.05). Conclusions: Hospitals of Tehran are at advanced level in terms of IPC, and the lowest score is related to the field of education, which needs more investigation and effort to improve it.